2012
DOI: 10.1139/v2012-007
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the aging and reactivation mechanism of tabun-inhibited acetylcholinesterase by using the quantum mechanical / molecular mechanical method

Abstract: The organophosphorous compound tabun is highly neurotoxic because of its irreversible inhibition on acetylcholinesterase (AChE). It is wildly used as a warfare agent in the military. In this work, the aging and reactivation mechanism of tabun-inhibited AChE were studied by using the quantum mechanical / molecular mechanical (QM/MM) method. Geometry optimization of the stationary points were performed at the B3LYP/6–31G(d) level. Single-point energies were computed at the B3LYP/6–311++G(d,p) level. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The superimposition of the model structures of oximes 16 and 17 docked into VX‐inhibited mouse AChE presented in Figure C shows that both oximes are bound in an elongated conformation with their 3‐hydroxy‐2‐pyridine aldoxime moieties within the active site, forming a π–π interaction with Trp86 in the choline binding site, as has been shown for numerous compounds containing an aromatic moiety, including bis‐pyridinium oxime reactivators (e.g., HI‐6, PDB ID: 5FPP), when bound in a non‐productive orientation in phosphylated mAChE . Although the distance between the oxygen atom of the oxime group and the phosphorus atom (6.59 Å for oxime 16 , 5.49 Å for oxime 17 ) is close to optimal (4–5 Å) for nucleophilic attack on the P=O moiety, both lack the optimal orientation of the oxime group for an in‐line nucleophilic attack (i.e., the oxime group does not approach the P=O moiety at an angle of approximately 180° with respect to the leaving group) . The only difference in the positioning of the two oximes is in the orientation of the morpholine ring, which implies that the higher reactivation efficiency (in terms of k r ) of oxime 17 over 16 could result from a better stabilisation of 17 in the productive conformation.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The superimposition of the model structures of oximes 16 and 17 docked into VX‐inhibited mouse AChE presented in Figure C shows that both oximes are bound in an elongated conformation with their 3‐hydroxy‐2‐pyridine aldoxime moieties within the active site, forming a π–π interaction with Trp86 in the choline binding site, as has been shown for numerous compounds containing an aromatic moiety, including bis‐pyridinium oxime reactivators (e.g., HI‐6, PDB ID: 5FPP), when bound in a non‐productive orientation in phosphylated mAChE . Although the distance between the oxygen atom of the oxime group and the phosphorus atom (6.59 Å for oxime 16 , 5.49 Å for oxime 17 ) is close to optimal (4–5 Å) for nucleophilic attack on the P=O moiety, both lack the optimal orientation of the oxime group for an in‐line nucleophilic attack (i.e., the oxime group does not approach the P=O moiety at an angle of approximately 180° with respect to the leaving group) . The only difference in the positioning of the two oximes is in the orientation of the morpholine ring, which implies that the higher reactivation efficiency (in terms of k r ) of oxime 17 over 16 could result from a better stabilisation of 17 in the productive conformation.…”
Section: Resultsmentioning
confidence: 62%
“…The morpholine ring is stabilised by an electrostatic interaction between its protonated nitrogen and the Asp70 carboxy group, and by multiple hydrogen bonds. Moreover, the distance and orientation of the oxime of the 3‐hydroxy‐2‐pyridine aldoxime moiety is optimal for an in‐line nucleophilic attack on the phosphorus atom . Surprisingly, when 16 is docked in the active site with the cyclosarin moiety in the alternative conformation, the binding mode of oxime 16 changes only slightly, predominantly in the alkyl linker, in comparison with its binding mode in the model with the predominant conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have also investigated catalytic profiles of AChE reactivation by oximes (Scheme C). QM/MM calculations showed that Glu334 stabilizes the pentavalent intermediate during reactivation . The Ganguly group assessed various reactivators by QM analysis, and showed that uncharged ones are kinetically more efficient .…”
Section: Introductionmentioning
confidence: 99%
“…The final stage of the multi‐tiered simulations involved computationally intensive QM/MM simulations, using density functional theory for the QM portion of the simulations. This kind of QM/MM simulation allows high‐fidelity studies of chemical reactions in enzymes and has been extensively used to study AChE catalysis, phosphonylation, aging, and reactivation with oxime antidotes before aging . To our best knowledge, this work is the first such QM/MM study of reactivation of the aged AChE adduct.…”
Section: Resultsmentioning
confidence: 99%